Hubungan Hubungan Pengetahuan Orang Tua terhadap Kualitas Hidup terkait Kesehatan Mulut Anak Down Syndrome - Nur Atika; Nurdiana Dewi; Galuh Dwinta Sari (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2024)
Background: Physical, motor, and intellectual retardation experienced by children with Down syndrome leads to low self-care skills and independence so that Down syndrome children depend on their parents in an effort to maintain oral hygiene. Parental knowledge will be one of the predisposing factors that shape the behavior of parents in maintaining children's oral health. Children's oral health can affect functional, psychological, and social aspects that impact the quality of life related to oral health. Objective: To analyze the correlation between the level of parental knowledge about dental and oral health to realize the quality of life in children with Down syndrome at SLB Banjarmasin. Methods: This study is an analytical observational study with a cross-sectional approach. The sampling method used was simple random sampling with 32 respondents from parents of children with Down syndrome at SLB Banjarmasin. The level of parental knowledge and quality of life related to oral health was determined using a modified oral health knowledge questionnaire and a modified Parent-Caregiver Perception Questionnaire (P-CPQ). Results: The results of the Spearman correlation test showed that there was a significant correlation between the level of parental knowledge and the quality of life of children with Down syndrome associated with oral health in SLB Banjarmasin with a significance value of 0.007 (p<0.05). The correlation coefficient value is 0.466. Conclusion: There is a correlation between the level of parental knowledge and the quality of life related to oral health in children with Down syndrome in SLB Banjarmasin City.